Oldest Known Shipwreck Reveals Splendors of the Bronze Age - Bass, George F.
Ulu Burun; 708: ram's head; 709: terebinth resin; 716: blue glass ingots; 722-725: cylinder seals; 726-727: ivory; 730-731: wooden writing board, diptych with ivory hinges.